STUDI KELAYAKAN JASA KONSULTANSI DI KABUPATEN BANYUMAS - Dwi Sri Wiyanti (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2008)
AbstractsConsultants are experts who help the owner according to expertise or function. Consultants consist of planning consultants, supervise consultant and construction management consultant. Government policy in Banyumas Distric that use third parties to assist and supervise local government project, in this case the consultant, as well as the small number of consulting services businessmen in Banyumas District giving opportunities to open a consulting business. According to the opportunity, a feasibility study within five years that use the amount of interest on bank deposits as reference to determine the value of profits and MARR (Minimum attractive Rate of Return) to evaluate the feasibility of the construction services business is made.For evaluation, NPV (Net Present Value), BCR (Benefit Cost Ratio), and IRR are calculated so that feasibility can be known for making business consulting services in Banyumas District which BEP (Break Event Point) will occurred in the fifth year. Keywords: Consultancy services Business, Planning, Supervision.